The Effect of Alternative vs. Focal Identity Accessibility on the Intent to Purchase Products: An Exploratory Study Based on Chinese Culture - Chen, Fei; Yan, Cheng Cheng; Wang, Lin; Lou, Xiao Jing (Frontiers in Psychology, 2022)
Much of early western research has focused on identity. A primed identity can inhibit the priming of other, alternative identities and also negatively affect the intention to purchase products related to those alternative identities. In western culture, individuals operate within a cultural framework that makes them more likely to prioritize their own goals and less likely to rely on environmental factors when evaluating others. Individuals are more likely to choose products that fit their primed identity. In the current study, we suggest that in collectivist Chinese culture, individuals may give priority to group-level goals and attach more importance to situational factors when evaluating others. Therefore, a primed identity may not necessarily inhibit the priming of alternative identities. In this research, we examine the association between a focal identity and alternative identities, with particular emphasis on the accessibility, discrepancies, and effects on purchase intention of alternative identities. We also examine the intent to purchase products related to the alternative identity versus the focal identity, developing a model with which to explore this construct. We test four hypotheses through experiments using an online questionnaire and analyzing the resulting data using SPSS 22.0 and the PROCESS macro modeling tool. The results are as follows: First, the association between a focal identity and alternative identity has a positive impact on the accessibility of the alternative identity. The clearer the alternative identity is, the greater the impact of the association between the focal identity and alternative identity on the latter's accessibility. Second, the accessibility of the alternative identity has a positive impact on the intent to purchase alternative identity- versus focal identity-related products. The greater the discrepancy between the focal identity and the alternative identity, the greater the impact on the intent to purchase alternative identity- versus focal identity-related products. The results of this study confirmed the interaction between identity association and the clarity of the alternative identity, as well as the influence of the accessibility of the alternative identity on the intent to purchase alternative identity- versus focal identity-related products. We contribute to the development of a theory on intention to purchase identity-related products.